Perceived discrimination and self-rated health in the immigrant population of the Basque Country, Spain - Elena Rodríguez-Álvarez; Yolanda González-Rábago; Luisa N. Borrell; Nerea Lanborena (Elsevier, 2017)
Objective: To examine the effect of perceived discrimination and self-rated health among the immigrant population in the Basque Country, Spain, and determine whether this effect varies according to region of origin, age, sex and education. Methods: Descriptive cross-sectional study. The study population included immigrants aged 18 and older residing in the Basque Country. Data from the 2014 Foreign Immigrant Population Survey (n = 3,456) were used. Log-binomial regression was used to quantify the association between perceived discrimination and self-rated health before and after checking for the selected characteristics. Results: Almost 1 in 10 immigrant adults reports perceiving discrimination. In adjusted analyses, the immigrants perceiving discrimination were almost were 1.92 more likely to rate their health as poor (prevalence ratio: 1.92; 95% CI: 1.44-2.56) than those who did not report discrimination. This association did not vary according to region of origin, age, sex or educational level. Conclusions: Perceived discrimination shows a consistent relationship with perceived health. Moreover, this association did not depend on the region of origin, age, sex or educational level of immigrants. These results show the need for implementing inclusive policies to eliminate individual and institutional discrimination and reduce health inequalities between the immigrant and native populations.